Happiness Across Cultures: An Exploratory Study of Indonesian, Indian, and American Perspectives - Athifah, Mutiah Rana; Gumelar, Gumgum; Yufiarti, Yufiarti (Jurnal Psikologi Islam dan Budaya, 2024)
This study aims to explore the different perspectives on the conception of happiness of Indonesians, Indians, and Americans. This study employs an exploratory qualitative approach using thematic data analysis with NVivo 12. Using purposive sampling, individual interviews were conducted with 7 participants aged between 25 to 50 years old. This study discerns divergent themes in happiness among three cultures, with notable similarities between Indonesians and Indians. Both cultures exhibit a pronounced emphasis on social ties and personal development and achievement. Additionally, religious and spiritual practices, positive outlook, and self-expression consistently emerge as significant factors shaping happiness in these cultures. Despite these similarities, each culture showed different contexts. In contrast, Americans showcase distinctive themes, prioritizing nature-connectedness, exploration, and autonomy which includes self-reliance. These findings underscore the pivotal role of cultural context in shaping perspectives on happiness, emphasizing the necessity for culturally tailored interventions to enhance happiness across diverse populations.